Analisis Perbandingan Kinerja Keuangan Perusahaan Sektor Properti Dengan Metode Du Pont & Economic Value Added (EVA) Kasus PT. Ciputra Surya Tbk Tahun 2016 – 2021 - Irma Setyawati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the company's financial performance with the Du Pont System and EVA approach for the period 2016 to 2021. And what things are related to this approach. The type of data used in this study is quantitative data which is secondary data, in the form of balance sheets and income statements. Based on these data, the research begins with a descriptive analysis of the financial performance of property companies which includes the condition of total asset turnover, net profit margin, return on assets, equity ratio and return on equity. The analysis is continued by using the EVA method which includes Capital, WACC, NOPAT. From the analysis with these two methods, it can be seen how well the company's financial performance is. By using the Du Pont System, it is known that the performance of PT. Ciputra Surya Tbk in terms of cross-sectional analysis of the company's ROE from 2016 to 2021 resulted in 2 positive (+) and 3 negative (-). This means that the company's ROE is still below the industry average. This is due to the ROE of PT. The MDLN (comparison) is positive while the value of Equity and Net Income is negative, which is one of the weaknesses of the Du Pont System. In Time Series the company's ROE was negative (-) in 2016, 2017 and 2018, meaning that the company's financial performance in that period was worse than the previous year. In 2016 and 2018 the company's ROE was positive (+), meaning that the financial performance in that period was better than the previous year. By using the EVA method, it is known that the financial performance of PT. Ciputra Surya Tbk in the period 2016 to 2021 in a Cross Section resulted in a positive EVA value (+). This means that the company's financial performance is better than the industry average (comparison company). By Time Series in 2016, 2017 and 2018, the company produced a negative EVA value (-). This means that the company's financial performance in that period was worse than the previous year. In 20014 and 2015 the company produced a positive EVA value (+), meaning that the company's financial performance in that period was better than the previous year.